РОЛЬ РИБОНУКЛЕАЗ У РЕГУЛЯЦІЇ ІМУННОЇ ВІДПОВІДІ - SHLYAKHOVENKO, V.; SAMOYLENKO, O.; VERBINENKO, A.; GANUSEVICH, I. (PH Akademperiodyka, 2024)
Ribonucleases (RNases) perform many different functions in living systems. They are responsible for the formation and processing of various ribonucleic acids (RNAs), including the messenger RNA and all types of microRNAs, and determine the duration of the existence of different RNAs in the cell and extracellular environment. RNases are ubiquitously expressed in many tissue types. This short review discusses the major types and main functions of RNases, their homeostatic functions, influence of transcription, immunomodulation, and the role of extracellular RNases in the immune defense mechanisms